Case-Based Reasoning for Pattern Recognition using Granular Information Generated by Active Hypercontours - Szczepaniak, Piotr S. (Wydawnictwo Politechniki Łódzkiej, 2021)
This paper presents a novel extension of the case-based reasoning (CBR) technique. In the proposed method, a case is defined using the concept of multidimensional information granule created by the active hypercontour. The granularity of information is expected to be justifiable. The paper explains the main principles of the method and discusses its usefulness with reference to the pattern recognition problem.
Keywords: pattern recognition; case-based reasoning; case-based classification; active hypercontours; information granules; hypercontour-based case specification; rozpoznawanie wzorców; wnioskowanie oparte na przypadkach; klasyfikacja oparta na przypadkach; aktywne hiperkontury; granulki informacyjne; oparta na hiperkonturach specyfikacja przypadku